4C abilities (critical thinking, communication, collaboration, creativity) of elementary school students in learning the Indonesian language - Febrina Dafit; Ronadia Febrianti Gurning; Mitha Dwi Anggriani (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
This research is motivated by students' inability to solve problems and express ideas, and students find it challenging to develop their abilities, especially in learning Indonesian. So, students need to be able to solve problems with their abilities. In this case, the education system must realize that students can think critically, communicate well, collaborate, and be creative. This research aims to describe the 4C abilities (critical thinking, communication, Collaboration, Creativity) of SDN 193 Pekanbaru students in learning Indonesian. This descriptive qualitative research uses data collection techniques, observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusions. The results show that students at SDN 193 Pekanbaru have 4C abilities, which include critical thinking skills, communication, Collaboration, and Creativity. However, even though students already have the 4C skills, there are still students who have not been able to master these four abilities due to a lack of interest in developing their skills, and at SDN 193 Pekanbaru, there are inclusion students. In this case, teachers always guide and hone students' abilities through various learning activities.